Исследование напряженно-деформированного состояния замкового соединения рабочих лопаток - Швецов, В.Л.; Литовка, В.А.; Пальков, И.А.; Пальков, С.А. (Проблемы машиностроения, 2012)
The analysis of the stress-strain state of the connection disc of 2nd degree cylinder medium-pressure steam turbine blades in the castle by the method of finite elements. The resalts are compared with experimental data